Exploring critical factors choice of piracy products: an empirical investigation on Malaysian customers’ - Haque, A. K. M. Ahasanul; Tarofder, Arun Kumar; Rahman, Sabbir (EuroJournals, Inc., 2011)
The primary attempt in this study was to explore the influencing factors of the Malaysian consumers toward the pirated products. To explore these factors, this study has conducted a survey among the Malaysian consumers. Structural equation modeling (SEM) approach was employed in order to examine the variables. From the result it is revealed that paths are related to the casual processes significantly. The results of the study showed that there is significant relationship between the consumers’ perception and the social influence, personality or believe, pricing and the economy toward the piracy. The outcome of this research showed a comprehensively integrated framework for policy maker and business enterprise to understand the dynamic relationships among dimensions of social influence, pricing, economy, and personality/belief to understand the consumers’ perception. However, further research is needed to examine these factors in Malaysia with additional samples before generalization can be made. Moreover, it is also needed to extend behavior intensions of consumers about piracy and pirated product.